Comparison of the Epidemiological and Clinical Characteristics of Hospitalized Children With Pneumonia Caused by SARS-CoV-2, Influenza A, and Human Adenoviruses: A Case-Control Study. (February 2022) - Liu, Miao; Han, Yuling; Sun, Jing; Wei, Xiaoling; Zhao, Xiuxia; Wang, Bing; Zhang, Yun; Ma, Xiang; Gai, Zhongtao
Background. This case-control study aims to investigate the clinical characteristics in pediatric patients with pneumonia infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A, and human adenoviruses (HAdVs). Methods. Hospitalized pediatric patients with pneumonia infected with SARS-CoV-2 at Wuhan Children's Hospital and pneumonia infected with influenza A, and HAdVs at Qilu Children's Hospital were compared. Clinical manifestations, laboratory examinations, and imaging characteristics were analyzed. Results. The proportions of hyperpyrexia (54.3%, 33.9%), cough (100%, 99.2%), wheezing (45.7%, 53.7%), diarrhea (31.4%, 14.9%), and fever (100%, 75.2%) in patients with influenza A and HAdVs were higher than those of patients with SARS-CoV-2 (9.4%, P < .001; 48.5%, P < .001; 0%, P < .001; 8.8%, P = .002; 41.5%, P < .001; respectively). Laboratory examinations revealed the proportions of leukocytosis (37.1%, 52.9%), abnormal rates of neutrophils (40%, 40.5%), and lymphocytosis (42.9%, 65.3%) in influenza A and HAdV pneumonia groups were significantly higher than coronavirus disease 2019 (COVID-19) group (0%, P < .001; 0%, P < .001; 0%, P < .001; respectively). The proportion of elevated procalcitonin (5.7%, 14%) in patients with influenza A and HAdVs was significantly lower than those in patients with SARS-CoV-2 (64%, P < .001). In chest computed tomography, ground-glass opacities near the pleura were more common in patients with COVID-19 than those in patients with influenza A and HAdVs (32.7% vs 0% vs 0%, P < .001). Conclusion. Fever, cough, and wheezing are more common in the influenza A and HAdVs groups, whereas procalcitonin and computed tomography findings are likely to be pronounced in COVID-19 pneumonia. It provides a variety of methods except polymerase chain reaction for differentiating COVID-19 pneumonia from influenza A and HAdVs pneumonia.